A Systematic Review of Knowledge, Attitudes and Practices among Healthcare Workers on Personal Protective Equipment against Covid-19 - Superzeki Zaidatul Fadilah; Ninuk Dian Kurniawati; Praba Diyan (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Coronavirus 2019 (COVID-19) is an acute respiratory disease that is emerging and spreading rapidly around the world. The rapid spread of COVID-19 poses new challenges in infection control. A comprehensive understanding of personal protective equipment (PPE) among health workers is essential. This study aims to conduct a systematic review of the knowledge, attitudes and practices of using PPE among health workers to prevent COVID-19 infection. The systematic review searched five electronic databases (Scopus, Pubmed, Science Direct, CINAHL, and Proquest) for previous studies published between 2019 and 2021. We found eleven studies that met the inclusion criteria in the review. Most of the health workers have good knowledge, positive attitudes and bad practices towards using PPE to prevent COVID-19 infection. The most important recommendation for increasing knowledge, attitudes and practices (KAP) is to equip health workers with a periodic training program on the use of PPE to combat COVID-19.